Diagnostic value of exome and whole genome sequencing in craniosynostosis. Issue 4 (24th November 2016) - Miller, Kerry A; Twigg, Stephen R F; McGowan, Simon J; Phipps, Julie M; Fenwick, Aimée L; Johnson, David; Wall, Steven A; Noons, Peter; Rees, Katie E M; Tidey, Elizabeth A; Craft, Judith; Taylor, John; et al.
Abstract : Background: Craniosynostosis, the premature fusion of one or more cranial sutures, occurs in ∼1 in 2250 births, either in isolation or as part of a syndrome. Mutations in at least 57 genes have been associated with craniosynostosis, but only a minority of these are included in routine laboratory genetic testing. Methods: We used exome or whole genome sequencing to seek a genetic cause in a cohort of 40 subjects with craniosynostosis, selected by clinical or molecular geneticists as being high-priority cases, and in whom prior clinically driven genetic testing had been negative. Results: We identified likely associated mutations in 15 patients (37.5%), involving 14 different genes. All genes were mutated in single families, except for IL11RA (two families). We classified the other positive diagnoses as follows: commonly mutated craniosynostosis genes with atypical presentation ( EFNB1, TWIST1 ); other core craniosynostosis genes ( CDC45, MSX2, ZIC1 ); genes for which mutations are only rarely associated with craniosynostosis ( FBN1, HUWE1, KRAS, STAT3 ); and known disease genes for which a causal relationship with craniosynostosis is currently unknown ( AHDC1, NTRK2 ). In two further families, likely novel disease genes are currently undergoing functional validation. In 5 of the 15 positive cases, the (previously unanticipated) molecular diagnosis had immediate, actionable consequences for either genetic or medical management (mutations in EFNB1, FBN1, KRAS, NTRK2, STAT3 ). Conclusions: This substantial genetic heterogeneity, and the multiple actionable mutations identified, emphasises the benefits of exome/whole genome sequencing to identify causal mutations in craniosynostosis cases for which routine clinical testing has yielded negative results.